IMPLEMENTATION OF MULTICULTURAL EDUCATION THROUGH ISLAMIC EDUCATION IN SCHOOLS/MADRASAS IN INDONESIA - Saiful Bahri; Nurhayati Nurhayati; Cut Intan Hayati; Nursri Hayati; Ahmad Liza (FORUM PAEDAGOGIK, 2026)
Multicultural Education is oriented towards Islamic Education which emphasizes accepting what it is against the times in accordance with ethics, morals and morals in Indonesia, so that in the view of Islam Multicultural Islamic Education which leads to mutual respect and embrace, mutual assistance from all forms of diversity, regardless, tribe, race, ethnicity, religion. In this study using literature studies with data collection techniques through thoughts and community leaders with a sociological approach that occurs in the field. The results of this study indicate that multicultural education through Islamic education can be implemented in schools/madrasas through strengthening the curriculum, methods, teaching materials and local wisdom activities in an area